Comparison of Training Using the Inside of the Foot and the Back of the Foot on Shooting Accuracy towards the Goal at Gasak FC - Syafii, Imam; Himawan, Agus; Purwoto, Septyaningrum Putri (Journal of Sport and Exercise Science, 2024)
Purpose: This research aims to evaluate and compare the effectiveness of training with the instep versus the outside of the foot on soccer shooting accuracy. Materials and Methods: An experimental design with pre-test and post-test measures was employed, involving two distinct treatment groups. The first group received training focused on using the instep for shooting, while the second group practiced shooting with the outside of the foot. The study included 30 soccer players, randomly assigned to these two groups. Shooting accuracy was assessed before and after an 8-week training period. Result: Results indicated that both training methods led to significant improvements in shooting accuracy, but training with the instep yielded a greater enhancement compared to using the outside of the foot. Conclusion: These results suggest that instep training is more effective for improving shooting accuracy and should be considered the preferred method for developing shooting skills in soccer players.